Treatment of Steinstrasse by Transureteral Lithotripsy - Rabbani, Sayed Mohammad Reza (Urology Journal, 2008)
Introduction: Extracorporeal shock wave lithotripsy (SWL) is an essential treatment for urinary calculi, but Post-SWL steinstrasse is a potential complication, especially in large-burden calculi. Our purpose was to evaluate the efficacy of transureteral lithotripsy (TUL) in the treatment of steinstrasse caused by SWL. Materials and Methods: Twenty-four patients with steintrasse following SWL were treated by TUL. The length of steinstrasse varied from 1.5 cm to 6 cm. The patients were followed up after TUL and failed treatment was considered if the steinstrasse was not cleared within 6 weeks. Results: Fourteen patients (58.3%) became stone free, of whom 8 had a double-J stent before SWL. Partial response was seen in 6 patients (25.0%). The remained 4 patients (16.7%) with failed TUL underwent open ureterolithotomy. One patient developed nonfunctioning kidney during the follow-up. Transureteral lithotripsy was successful in 6 out 8 patients with type 1, 8 out of 12 with type 2, and none of those with type 3 steinstrasse. All of the successful cases of TUL were in the patients with lower ureteral calculi. Conclusion: Successful treatment of steinstrasse by TUL can be achieved in less than two-thirds of the cases. Type and location of steinstrasse may influence the outcomes. This complication seems sometimes to be troublesome and may even cause kidney loss.